Internal whistleblowing systems without proper sanctions may backfire - Sebastian Krügel; Matthias Uhl (Journal of Business Economics, 2023)
Internal whistleblowing systems are supposed to fight misconduct within organizations. Because it is difficult to study their efficacy in the field, scientific evidence on their performance is rare. This is problematic, because these systems bind substantial resources and might generate the erroneous impression of compliance in a company in which misconduct is prevalent. We therefore suggest a versatilely extendable experimental workhorse that allows the systematic study of internal whistleblowing systems in the lab. As a first step, we tested the efficacy of whistleblowing systems if internal punishment for misconduct is mild and hesitant which is usually the case in practice, as several fraud surveys confirm. Our results show that under these conditions almost nobody blew the whistle, and misconduct occurred even more frequently with than without a whistleblowing system. The institutionalization of whistleblowing seemed to crowd out the intrinsic motivation to act compliantly. Moreover, when a whistleblowing system was either unavailable or not used, misconduct was highly contagious and spread quickly. Yet, when we implemented severe and ensured punishment for misconduct, whistleblowing systems could deter wrongdoing. In such a setting, people were willing to blow the whistle and the prevalence of misconduct dropped substantially. Altogether, our results highlight the interaction between institutions and preferences and can support the design of compliance measures within organizations. For compliance managers a key takeaway is that if companies preach a zero-tolerance policy, they should practice it as well. Otherwise, they might even worsen the situation.
Keywords: 650; Misconduct; Whistleblowing; Punishment; Crowding out